A Comparative Study of On-Campus and Off-Campus Internet Facilities (American Journal of Smart Technology and Solutions, 2023)
This study aimed to compare the lived experiences of the graduate school students in accessing internet facilities inside and outside the university campus. Qualitative method using phenomenology as a design was utilized. The internet services in two campuses were compared. Aspects of comparison between the two lenses started with the on-campus followed by the off-campus were presented in terms of; internet connection: dawdling versus fast; Wi-Fi connection: difficult to access versus accessible; network: low versus hassle-free; accessibility: limited versus limitless; adequacy of facility units: discomfort versus comfortable; expert’s and mentor’s guidance: available versus difficult to avail; research environment: safe versus unsafe; power supply: sustainable versus susceptible to interruption. These results implied an urgency of the university to look into the problem that the students are facing in accessing internet facilities for their research activities.